Estimation of Monocytes and Platelets CD 36 Expression Levels in Patients with Type 2 Diabetes Mellitus, Sudan - Mohammed Ali, Eglal Elamein; M. Dafalla, Abuagla; Abdelhameed Mohammed, Yousif; Nour, Bakri Yousif Mohamed (British Journal of Healthcare and Medical Research, 2023)
Diabetes mellitus (DM) is a global health concern affects all ages. Over the past few decades diabetes mellitus is a prevalent, potent devastating, medical problem that has an increasing prevalence. CD36 is a multifunctional signaling cellular receptor with different ligands specificity. It is expressed on different cells including macrophages, platelets and monocytes. Objective: This a case control study aimed to estimate monocytes/platelets CD36 levels in patients with type 2 diabetes mellitus in the period between 2019 and 2022. Methodology: 70 samples collected from type 2 diabetic patients attending Zeenam Specialized center, Khartoum, Sudan. And 30 samples collected from healthy individuals as control group. 5ml of venous blood were collected from the participants, 2.5 ml were put into a labeled EDTA containers; whole blood were collected to measure HbA1C using I chroma; Boditech Med Inc., and monocytes/platelets CD36 expression levels using CYTOMICs FC 590, Beckman coulter at Flow cytometery laboratory, Khartoum, Sudan. Another 2.5 ml were put into labeled sodium fluoride container to measure FBG using Biosystem chemistry analyzer BTS-302. Results: This study showed that the levels of FBG, HbA1C and platelets CD36 expression were significantly higher in type 2 diabetic patients compared with control group (P = 0.000, P = 0.001 and P = 0.012) respectively. And there are no statistical significant difference in expression level of monocytes CD36 between cases and control (P = 0.366). Also this study found that monocytes CD36 has a statistically significant correlation with fasting blood glucose (P = 0.009), and it is not correlated with HbA1C (P = 0.547). Platelets CD36 has a statistically significant correlation with fasting blood glucose, HbA1C and monocytes CD36 (P = 0.000) (Table 4). Conclusion: This study concluded that platelets CD36 expression was significantly higher in type 2 diabetic patients compared with control group. And there are no statistical significant difference in expression level of monocytes CD36 between cases and control. Also it concluded that monocytes CD36 have a statistically significant correlation with fasting blood glucose, and it is not correlated with HbA1C. Platelets CD36 have a statistically significant correlation with fasting blood glucose, HbA1C and monocytes CD36.